GRASSROOTS SOLIDARITY IN REVITALISING RURAL ECONOMY IN ASIA, DRAWING LESSONS FROM THREE CASE STUDIES IN INDIA, INDONESIA AND CHINA - Jayasooria, Denison (Sociedade e Território, 2022)
As Asia is experiencing rapid economic development, it is also impacted by both positive and negative aspects. Rapid urbanisation and the growth of mega cities in Asia is impacting the quality of life of the poor in these cities as well as impacting negatively the rural areas and abandoned farming land. However within Asia are grassroots community experiences which are revitalising the rural economy through community organising, women empowerment and creative interventions through sustainable business models and good governance principles. Three case studies highlighted from India, Indonesia and China to illustrate this and draw lessons from transforming our economic priorities toward social solidarity economy.